Pekerja Rumah Tangga (PRT) dan penerimaan terhadap makna spiritual dalam tayangan religi di televisi - Reny Triwardani; Panji Dwi Asrianto (Masyarakat, Kebudayaan dan Politik, 2014)
Religious soap opera is a tv shows that display story and culture which related to Islam within its story line. Different representations within religoius soap opera could lead to various interpretations. The text displayed posses dynamic values, particularly about how a text receive a value after being consumed by its audience. This research aims to describe audience acceptance level of spiritual meaning in religion tv shows. TV programs that had been observed were Layar kemilau (MNC TV) and sinema Pintu Taubat (Indosiar). This research uses descriptive qualitative method with in depth interview using 3 informants. Stuart Hall acceptance analysis was was used to identify two from three different affeptance models; dominant and negotiating. This research identify dominant and negotiating audience as informant to answer the research question. Informant background, peer group influence, the need of enterainment and audience gender were founded as significant inlfluencer of domestic workers’ decision to watch religion soap opera in TV. This research shows that different interpretation obtained the audience can be reciprocal or contradict with the content of religious soap opera in TV